Fauna bentónica asociada a una pradera de Thalassia testudinum (Hydrocharitaceae) en el Parque Nacional Morrocoy, Venezuela - Rodríguez, Carmen (2000)
The benthic fauna and diel variation in a shallow seagrass bed (Thalassia testudinum) were studied in Playa Mero, Venezuela Samples of organisms and sediments were taken using PVC cylinders, 5 cm in diameter, along a transect perpendicular to the coast Seagrass cover, shoot density and biomass were estimated. The sea grass cover was homogeneous a10ng the transect. The intermediate zone had the highest number of shoots and of above- ground and rhizome biomass. Composition and.abundance of benthic organisms were related with seagrass and sediment characteristics. Sediment organic matter contentand organism abundance were highest near the shore. Molluscs, polychaetes, oligochaetes and nematodes were the most abundant groups. Species richness-was higher in daytime (40 versus 28 at night). Gastropods were the most abundant organisms both at day and night while polychaetes and crustaceans increased during the day, and holoturids were more numerous at night.